A model for predicting the stress–strain relation of PVC-CFRP confined concrete stub columns under axial compression. (August 2020) - Fang, Yuan; Yu, Feng; Guan, Yucong; Wang, Zhongwen; Feng, Chaochao; Li, Dongang
Abstract: This paper presented an experimental investigation on the Polyvinyl Chloride-Carbon Fiber Reinforced Plastic (PVC-CFRP) Confined Concrete (PVC-CFRP-CC) stub columns under axial compression. A total of two PVC Confined Concrete (PVC-CC) columns and ten PVC-CFRP-CC columns were conducted. The effect of spacing of CFRP strips on mechanical behaviors of PVC-CFRP-CC stub columns was investigated. Meanwhile, the influence on mechanical behaviors was also analyzed in terms of equivalent confining effect coefficient. Test results demonstrated that PVC-CC stub columns failed by the buckling of PVC tube while the PVC-CFRP-CC stub columns were damaged by the tensile fracture of CFRP strips and the cracking of PVC tube. The bearing capacity of PVC-CFRP-CC stub columns increased gradually as the equivalent confining effect coefficient increased while the bearing capacity decreased with the increase of spacing of CFRP strips. With the decrease of spacing of CFRP strips or the improvement of equivalent confining effect coefficient, the confinement of PVC-CFRP tube on core concrete enhanced, the ultimate compressive strain of the PVC tube and the ultimate tensile strain of the CFRP strips increased. Based on a large and up-to-date test data including measured data in this study and data collected from the literatures, a modified model for conveniently predicting the stress–strain relation of PVC-CFRP-CC stub columns was established and verified the test data with good agreement.